Hydrothermally extracted nanohydroxyapatite from bovine bone as bioceramic and biofiller in bionanocomposite - Bano, Nazia (2019)
Bones have an extraordinary capacity to restore and regenerate in case of minor injury. However, major injuries need orthopedic surgeries that required bone implant biomaterials. In this study, n-HAP powder was extracted from bovine bone by hydrothermal and calcined at different calcination temperatures (600-1100°C) without the use of solvents. The n-HAP powders produced were used to fabricate two types of biomaterials (HAP bioceramics and PLA/n-HAP bionanocomposite). The raw-HAP and calcined n-HAP powder samples were compacted into green bodies and were sintered at various temperatures (1000-1400°C) to produce HAP bioceramics. The best calcined n-HAP was mixed with PLA by melt mixing and injection moulding to fabricate PLA/n-HAP bionanocomposite. Characterizations of the n-HAP powder, n-HAP bioceramics and PLA/n-HAP bionanocomposite samples were done by Thermogravimetric analysis (TGA), X-ray diffraction (XRD), Fourier transforms infrared (FTIR), Field emission scanning electron microscopy (FESEM), Energy-dispersive x-ray spectroscopy (EDX), X-ray fluorescence (XRF) spectroscopy, universal testing machine (UTM) and melt flow index (MFI) analyses. TGA data revealed that n-HAP was thermally stable at 1300ºC. The extracted n-HAP powder was highly crystalline and crystallite size was in the range of 10-83 nm as confirmed by XRD. Density and hardness of the n-HAP bioceramics increased as sintering temperature increased and showing maximum values at a temperature of 1400°C. The results of PLA/n-HAP bionanocomposite revealed that the higher n-HAP loaded (at 5wt%), the lower the tensile strength of bionanocomposite due to poor interfacial adhesion. The interfacial adhesion was improved by loading of 1.0 wt% maleic anhydride (MAH) as a compatibilizer. The biocompatibility of bionanocomposite was evaluated in simulated body fluids (SBF). The results showed that apatite layers were grown on the surfaces of both biomaterials. Therefore, both biomaterials formulated shall be promising medical biomaterials for orthopedic applications.